A Pilot Study of Preparedness for Medical Emergencies in Urban Private Dental Practices in Malaysia - Nalisha Mohamed Ramli; Nor Azura Ahmad Tarmidzi; Ahmad Dzulfikar Samsuddin; Nurul Izza Idaham; Ahmad Zharif Ibrahim (Univ Sains Malaysia, SCH Dental Sciences, 2024)
Indexed by WOS/ Scopus